The Need for Basic Skills in Colleges and Universities - Crawford, June Justice ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
The need for basic skills instruction at the college level is discussed in light of the history of United States educational standards, changes in college student populations, and indicators of need for basic skills programs. Historically, it appears as if basic skills instruction has always been needed at the college level to aid the underprepared student. World War II and the civil rights movement are cited as having caused drastic changes in the character and composition of the student population. It is suggested that objections to basic skills instruction at the college level have grown as the need has grown and may be attributed to the increased cost of providing this service. Declining enrollments, lowered admissions standards, and the growing number of nontraditional students has increased the need for basic skills instruction during a time of financial exigency. The basic skills program implemented at Niagara University in New York is described. The University established a learning center and students in the program are closely monitored. (SF)
ERIC Note: Paper presented at the Meeting of the International Reading Association (Atlanta, GA, April 26, 1979).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Academic Standards; Admission (School); Basic Skills; College Students; Educational Economics; Educational History; Enrollment Trends; Higher Education; Learning Laboratories; Minority Groups; Nontraditional Students; Program Descriptions; Reading Skills; Remedial Programs; Student Characteristics; Writing Skills; Niagara University NY; Speeches/Meeting Papers